Detecting molecular changes in Vimy flaxseed protein structure using synchrotron FTIRM and DRIFT spectroscopic techniques: Structural and biochemical characterization. Issue 5 (2009) - Doiron Doiron, K. J. K. J.; Yu Yu, P. P.; Christensen Christensen, C. R. C. R.; Christensen Christensen, D. A. D. A.; McKinnon McKinnon, J. J. J. J.
Abstract : Mid-IR techniques were used to characterize any changes that occurred on a molecular level in flaxseed that had been heated using an autoclave. The objectives were to investigate the effects of autoclave heating on differences in diffuse reflectance infrared Fourier transform (DRIFT) and synchrotron-based Fourier transform infrared microspectroscopy (SFTIRM) based measurements of the protein α -helix to β -sheet ratio for flaxseed ( Linum usitatissimum ), cv. Vimy. Hierarchical cluster analysis (CLA) and principal components analysis (PCA) were also conducted to identify molecular differences in the DRIFT spectra. Flaxseed samples were kept raw for the control or autoclaved in batches at 120°C for 20, 40 or 60 min for treatments 1, 2 and 3, respectively. DRIFT analysis of protein secondary structure ratios showed a decrease ( P < 0.05) in the α -helix to β -sheet ratio for the whole seed while the results from synchrotron SFTIRM spot data from the endosperm tissue in flaxseed showed autoclaving had the opposite effect ( P > 0.05). CLA and PCA were successfully used to make distinctions between the different treatment spectra and showed enhanced sensitivity upon selection of a smaller spectral window to include only the amide I and II portion of the IR spectrum. Our results indicated that autoclaving had a great enough effect on the mid-IR spectrum of flaxseed to identify the altered α -helix to β -sheet ratio and subsequently differentiated between the treatments using PCA and CLA suggesting greater sensitivity of mid-IR spectral methods in identifying the effect of heat treatment on protein secondary structure. Future study is needed to quantify the relationship between protein secondary structure and protein functionality.